Perdón y reconciliación en el contexto del post-conflicto en Colombia (2020)
Colombian society is in the process of transitioning to a period called "postconflict" or "post-agreement" because of the signing of the peace agreement with the Fuerzas Armadas Revolucionarias de Colombia - FARC. This situation represents a challenge for all disciplines, especially the social sciences, in coordinating effo rts to guarantee peace. Among these challenges is the reconstruction of the social fabric through processes of forgiveness and reconciliation as pillars in the consolidation of a just and peaceful society. In this sense, the present paper aims to give a conceptual approach to these two constructs, as well as sorne methodological considerations that can be useful in this process of social reconstruction.